Interaction effects of washing and abrasion on thermal protective performance of flame-retardant fabrics. Issue 1 (2nd January 2021) - Wang, Lijun; He, Jiazhen; Lu, Yehu; Jiang, Shumin; Wang, Min
Abstract : In this study, common flame-retardant fabrics were treated with single washing or abrasion and their interactions to simulate wearing away during use. The changes in thickness, mass/m 2 and protective performance of the fabrics under both flame and radiation environments were evaluated. Results demonstrated that the protective performance was firstly increased after washing or abrasion, and then decreased with further increasing washing or abrasion cycles. After certain treatment cycles, the combined effect of washing and abrasion was significantly greater than the single effect of washing or abrasion alone. The interaction modes of washing and abrasion also showed significant differences in protective performance under a flame test. Under radiation exposure, the effect of combined washing and abrasion was more obvious. There was a positive correlation between the fabric weight and its protective performance with different treatments. The findings provide useful guidance for the actual use and maintenance of protective clothing.